2021
DOI: 10.21037/qims-20-916
|View full text |Cite
|
Sign up to set email alerts
|

Exploring diagnostic performance of T2 mapping in diffuse glioma grading

Abstract: Background: To evaluate the diagnostic performance of T2 mapping in differentiating WHO grade II glioma from high-grade glioma (HGG).Methods: We conducted a single-center, retrospective diagnostic study. Confirmed diffuse glioma (WHO grade II-IV) patients who underwent post-contrast T1-weighted imaging, T2-weighted imaging, and T2 mapping were included. All diagnoses were based on histological and molecular tests. Seventy-five percent of cases were subsampled to generate receiver operating characteristic (ROC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Our study demonstrated that quantitative T2 values could differentiate EMC from normal endometrium, which was consistent with tumors in other organs ( 8 , 10 , 16 , 17 ). As for the ADC values, the same applied with the quantitative T2 values, a lower value is suspected to be cancer.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our study demonstrated that quantitative T2 values could differentiate EMC from normal endometrium, which was consistent with tumors in other organs ( 8 , 10 , 16 , 17 ). As for the ADC values, the same applied with the quantitative T2 values, a lower value is suspected to be cancer.…”
Section: Discussionsupporting
confidence: 85%
“…T2 mapping can be used to analyze the changes in the composition of the tissue by measuring the T2 relaxation time, which is related to the water content in the tissue ( 16 ). Previous researchers have reported the value of T2 mapping in the detection and prediction of tumor histopathological features ( 16 , 17 ), but few quantitative studies have focused on T2 mapping in EMC. In this study, T2 mapping can be used to visualize the morphological structure of the myometrium, especially the JZ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have proposed grading gliomas based on quantitative parameters of magnetic resonance imaging (MRI) techniques, such as magnetic resonance (MR) spectroscopy, perfusion imaging, T2 mapping, and diffusion-weighted imaging (DWI). Of these methods, DWI is the most sensitive and has great potential for grading tasks (4)(5)(6)(7)(8). Many DWI models have been proposed over the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, quantitative MRI techniques have been used for evaluating the changes of the microenvironment in fibrotic endometrium 16,17 . Quantitative T2 relaxation time (spin–spin relaxation time), the time constant representing the decay of transverse magnetization, is obtained by a T2 mapping MRI sequence, and can reflect water accumulation and blood volume within tissues 18,19 . T2 mapping has been successfully applied to evaluate myocardial fibrosis and liver fibrosis 20,21 .…”
mentioning
confidence: 99%